Jumping Robot with Initial Body Posture Adjustment and a Self-Righting Mechanism. (15th June 2016) - Chen, Kewei; Chen, Diansheng; Zhang, Ziqiang; Wang, Min
To improve jumping performance, this paper presents a jumping robot with initial body posture adjustment and a self-righting mechanism. A segmental gear, stretching and triggering a spring for the storage and rapid release of energy, is used for the jumping mechanism. Pairs of front and hind supporting legs are used for the initial body posture adjustment. One end of each jumping leg is connected to a spring, while the other end is connected to the necessary wiring. In this way, the robot can correct its orientation from an upside down posture upon landing, simultaneously recovering its jumping legs and storing energy. Experimental results indicate that a jumping robot with a size of 78 mm × 43 mm × 40 mm and a weight of 30 g can jump across an obstacle with a controlled trajectory. It can also control its air pitching posture using the initial body posture adjustment. In addition, the robot can recover its body posture on the ground and store energy for a second jump. This work may provide useful data for further research into take-off posture control mechanisms.